Calf aversion to hot-iron disbudding - Ede, Thomas (Sci Rep, 2019)
Dairy calves are routinely disbudded by cauterization with a hot iron. To mitigate the intra-operative and initial post-operative pain associated with this procedure some farmers provide calves general and local anesthetics, but it is unknown if the procedure remains aversive. We used a place-conditioning paradigm to assess aversion caused by hot-iron cautery with a local anesthetic compared to a sham procedure. A test area was divided into three equally sized pens: two ‘treatment’ pens with distinct visual cues were connected by a central ‘neutral’ pen. Each calf went through the disbudding procedure and a 6-h recovery period in one treatment pen and the control procedure in the other treatment pen. In three tests (48, 72 and 96 h after the second treatment), calves could freely roam among the pens until they chose to lie down, ending the session. Calves spent less time in either of the treatment pens compared to the central pen. When only comparing the two treatment pen, calves spent less time in the disbudding pen, especially during the first test. Calves were also less likely to lie down in the pen associated with the disbudding procedure. We conclude that even with the use of a local anesthetic, hot-iron disbudding is salient and aversive for calves, indicating the need to refine or avoid the procedure.